Kesan program kesejahteraan psikologi menggunakan kaedah bermain kepada kanak kanak Sekolah Rendah / Norsayyidatina Che Rozubi - Norsayyidatina , Che Rozubi (2017)
This study was conducted to determine the effect of Psychological Well-Being Program intervention using play methods among primary school children. The subject was eleven year-old students (N = 123) from schools in Selangor. The aim of the study was to identify the impact of the program on psychological wellbeing, life satisfaction and self-esteem among the control and the treatment group of primary school children. The study also seek to determine gender differences between the treatment and the control groups. In addition, this study was also conducted to examine the relationship between psychological well-being, life satisfaction and self-esteem. This is to ensure that the intervention program for the treatment group could be sustained. By using true experimental study design, selection of study subjects was randomly divided between the treatment and the control groups. The Psychological Wellbeing Scale, Life Satisfaction Scale and Self-Appreciation Scale were used in this study. Findings were analyzed using MANCOVA, Pearson and Repeated-Measurement - MANOVA. The study found that the Psychological Wellbeing Program improved psychological well-being, life satisfaction and self-esteem of primary school children. From the aspect of program impact, it is showed that there were similar results between male and female children after the program was implemented. The study also found there is a relationship between self-esteem and psychological well-being of primary school children. In addition, the program managed to sustain the level of psychological well-being, life satisfaction and self-esteem of children for a longer period of time.